2009
DOI: 10.1002/pi.2556
|View full text |Cite
|
Sign up to set email alerts
|

Ageing of poly(lactic acid) films plasticized with commercial polyadipates

Abstract: BACKGROUND: Amorphous poly(lactic acid) (PLA) was plasticized with two polyadipates with different molar masses. Some physical properties were studied over time to evaluate the stability of these blends. The aim of this study was to improve PLA ductility and consider the feasibility of its use in flexible films for food packaging.RESULTS: The addition of polyadipates caused a decrease of the glass transition temperature (Tg) and an increase of PLA chain mobility. Samples with Tg values above the storage temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 32 publications
(32 reference statements)
4
47
0
1
Order By: Relevance
“…Some studies showed a decrease in water and oxygen permeability for different types of PLA (e.g. totally amorphous, semicrystalline, with/without plasticizers) as a result of PLA structure densification during physical ageing [56][57][58]. Based on these considerations, it could be hypothesized that such decrease in the diffusion properties originated from the acceleration of physical ageing during CO 2 sorption.…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…Some studies showed a decrease in water and oxygen permeability for different types of PLA (e.g. totally amorphous, semicrystalline, with/without plasticizers) as a result of PLA structure densification during physical ageing [56][57][58]. Based on these considerations, it could be hypothesized that such decrease in the diffusion properties originated from the acceleration of physical ageing during CO 2 sorption.…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…The elongation at break decreased slightly for the PLA/lignin SARKANDA formulation with the increase of lignin content. However, as PLA on itself is already a brittle material [54][55][56][57][58], further decrease was difficult to detect. The measured strain at break values of neat PLA data were in agreement with the data given by the provider in the PLA 2002D datasheet and with literature results [56,59].…”
Section: Composite Materials Characteristicsmentioning
confidence: 99%
“…Concerning food 65 contact materials, there are several requirements to be 66 satisfied by additives, such as being non-toxic substances, 67 showing good miscibility with the polymer, providing high 68 tensile strength, ductility, and suitable thermal properties. [10]o r 75 polyadipates [11,12], but their compatibility with PLA 76 is limited and the possibility of incorporation with no 77 phase separation is restricted to concentrations lower than 78 20 wt% limiting their potential properties in food pack-79 aging. In general, it has been accepted that amounts from 80 10 to 20 wt% of plasticizers are required to provide a 81 substantial reduction of the PLA glass transition tempera-82 ture (T g ) as well as to obtain adequate mechanical prop-83 erties for films manufacturing.…”
Section: Details Requiredmentioning
confidence: 99%
“…This is an 289 important parameter for further blending with PLA. In 290 general, higher viscosities result in more difficulties during 291 blending, but it should be pointed out that the obtained 292 value for this parameter ranges in the same order to those 293 normally presented by polyadipates, which were success-294 fully blended with PLA in previous works [11,12]. 295 The number-average molar mass (Mn) of OLAs ranged 296 from 671 to 957 Da, with polydispersity indexes below 1.5 297 in all cases (Table 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation